Is the FHA Creating Sustainable Homeownership?. (14th October 2015) - Caplin, Andrew; Cororaton, Anna; Tracy, Joseph
<x xml:space="preserve">Abstract</x> We produce first estimates of the sustainability of homeownership for recent Federal Housing Administration (FHA) borrowers. Unfortunately, the FHA does not produce its own statistics on sustainability. Neither does it permit researchers access to its data on internal refinances. This imposes significant barriers to entry for researchers who wish to track FHA borrower performance over time. We carefully construct the required tracking data to overcome this barrier. We forecast that no more than 75% of the 2007–2009 vintages of FHA borrowers will be able to successfully exit the FHA system. Our work raises questions about FHA's role, its accounting and its accountability.